2019
DOI: 10.1155/2019/8419810
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Mediates Anxiety-Like Behavior Induced by High Caffeine Intake in Zebrafish: Protective Effect of Alpha-Tocopherol

Abstract: Anxiety is a common symptom associated with high caffeine intake. Although the neurochemical mechanisms of caffeine-induced anxiety remain unclear, there are some evidences suggesting participation of oxidative stress. Based on these evidences, the current study is aimed at evaluating the possible protective effect of alpha-tocopherol (TPH) against anxiety-like behavior induced by caffeine (CAF) in zebrafish. Adult animals were treated with CAF (100 mg/kg) or TPH (1 mg/kg)+CAF before behavioral and biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 36 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…The results were consistent with some studies. For example, a study found that the treatment of caffeine could increase the level of MDA in the zebrafish brain (de Carvalho et al., 2019). Several studies showed that ellagic acid and gallic acid could ameliorate liver steatosis in mice (Sousa et al., 2020; Zhang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The results were consistent with some studies. For example, a study found that the treatment of caffeine could increase the level of MDA in the zebrafish brain (de Carvalho et al., 2019). Several studies showed that ellagic acid and gallic acid could ameliorate liver steatosis in mice (Sousa et al., 2020; Zhang et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The flowers of the plant contain quercetin, and isoquercetin, while stem contains beta-sitosterol. Alpha-tocopherol exerted a protective effect against high-caffeine induced anxiety effects in Zebrafish (34). Quercetin is evident to reduce cortical GABAergic transmission (35) and exert an anxiolytic effect on experimental animals (36).…”
Section: Metabolitesmentioning
confidence: 94%
“…Zebrafish were cold-anesthetized and injected intra-abdominally with either saline solution (SAL, 0.9%) or 1 mg/Kg ACEA dissolved in 0.005% DMSO. Drug dilution and treatments were performed 30 min before the behavioral experiments to assure drug distribution and reach in zebrafish brain as performed by de Carvalho et al ( 2019 ) and Assad et al ( 2020 ). The fish were then transferred to individual plastic aquaria, in which they were kept for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The product of lipid peroxidation was determined in the supernatant using 20 mM of pH 7.4 Tris-HCl, 10.3 mM of N-methyl-2phenylindole (NMFI), and methanesulfonic acid at 45°C. The lipid peroxidation was analyzed based on the standard curve of the malondialdehyde (MDA) concentrations, measured by its absorbance at a wavelength of 570 nm (de Carvalho et al, 2019 ). The MDA concentration was quantified in nmols per milligram of protein determined using the Bradford method.…”
Section: Methodsmentioning
confidence: 99%